مجلة حوليات التراث العدد 20 - Annales du patrimoine (Annales du Patrimoine, 2020)
حوليات التراث مجلة علمية محكمة ثلاثية اللغة تصدر بمشاركة الباحثين الجامعيين والمستقلين في الآداب واللغات والعلوم الإنسانية. تعنى مجلة حوليات التراث بمختلف ميادين التراث: الأدب واللسانيات والدين والفلسفة والفن. تصدر بالعربية والفرنسية والإنجليزية مرة واحدة في السنة وتنشر حصريا على شبكة الإنترنت. تسهر اللجنة العلمية على تقييم المقالات التي تودع إلى هيئة التحرير. يشمل كل عدد على ملف محوري ومقالات متفرقة. تأسست مجلة حوليات التراث في سنة 2004 بجامعة مستغانم (الجزائر) وصدرت بطبعتين، ورقية إلكترونية. - Annales du patrimoine (Annals of Heritage) is a trilingual academic journal published with the participation of researchers in literature, languages and humanities. The journal is devoted to different areas of heritage: literature, language, spirituality, philosophy, art. It appears in Arabic, French and English once a year and distributed exclusively online. A scientific committee evaluates articles submitted to the editors. The journal includes a thematic renewed each number and variable items. Annales du patrimoine/Hawliyyat al-Turath was established in 2004 at the University of Mostaganem (Algeria) in two editions, paper and electronic.